Literature Review: Meningkatkan Creative Thinking Skill melalui Pembelajaran Treffinger - Khoirun Analisa; Abdul Muhid (Jurnal Studi Guru dan Pembelajaran, 2024)
Education is a major component in national development that functions as a means of developing human resources. In the 21st century, technological advances facilitate access to education, but there are still challenges in improving students' knowledge and skills. The modern learning paradigm emphasizes creative, analytical, cooperative and collaborative thinking skills. Students' creative thinking skills in Indonesia are still lacking. Many factors hinder students' creative thinking abilities, including conventional or teacher-centered learning methods. The Treffinger learning model is proposed as a solution to improve students' creative thinking skills with three important elements: independent learning, idea generation, and creativity. This study aims to analyze the urgency of improving creative thinking skills through treffinger learning. This study uses a qualitative method through a systematic review with data obtained from a literature review. To achieve the research objectives, relevant sources are needed to answer the research questions and other related references are collected through the search process. Furthermore, the analysis is carried out by collecting various scientific journals and books related to the research variables. The results of the literature review study indicate that treffinger is independent learning, the main key is finding concepts or information through events experienced by students during teaching and learning activities. From the results of the analysis of several references obtained, it is known that this treffinger learning makes the subject matter easier to understand and remember the material. In its application, the treffinger learning model integrates cognitive dimensions and effectively finds the direction of problem solving to be taken. The results of the analysis can be concluded that Treffinger learning is effective in improving creative thinking skills in all subjects and can be applied to students and college students.